2020
DOI: 10.1080/10739149.2020.1765175
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of 8-hydroxyquinoline in a cosmetic product on a glassy carbon electrode modified with 1-amino-2-naphthol-4-sulphonic acid

Abstract: A new voltammetric method was developed for the simple, rapid and inexpensive determination of 8-hydroxyquinoline (8HQ) on a modified electrode obtained by the electrodeposition of 1-amino-2-naphthol-4-sulfonic acid (ANSA) on the surface of a glassy carbon (GC) electrode. The electrode interfacial properties were investigated by electrochemical impedance spectroscopy (EIS). The electrochemical response of the ANSA-GC electrode toward 8-hydroxyquinoline was investigated by the use of square wave voltammetry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the studies of determination of various ions or compounds, choosing the appropriate electrolyte and its pH is important [65]. The supporting electrolyte solution is effective on the values of peak potential and peak current in the voltammetric measurements [66, 67]. Most previous literature reports indicate that a neutral [28, 68] or slightly alkaline [1, 69, 73] media was used as the supporting electrolyte solution for the determination of L‐DOPA and PAR.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies of determination of various ions or compounds, choosing the appropriate electrolyte and its pH is important [65]. The supporting electrolyte solution is effective on the values of peak potential and peak current in the voltammetric measurements [66, 67]. Most previous literature reports indicate that a neutral [28, 68] or slightly alkaline [1, 69, 73] media was used as the supporting electrolyte solution for the determination of L‐DOPA and PAR.…”
Section: Resultsmentioning
confidence: 99%
“…FT‐IR measurements were used to characterize 4HQ3CA/GC and investigate the binding sites of the 4HQ3CA film to the GC surface [39]. Bare GC electrode surface spectra were obtained and taken away from the modified surface spectra to get the film spectra of the grafted 4HQ3CA.…”
Section: Resultsmentioning
confidence: 99%
“…6 Currently, the effects of 8-HQ on human health are still being investigated, but it has been reported that the carcinogenic effect of 8-HQ can be observed after implantation in the bladder of mice. 7 Due to the widespread use of 8-HQ in cosmetics and its potential toxicity to mammalian cells, European Union Council Directive 76/768/EEC stipulates that 8-HQ is not allowed to be used in cosmetics other than hair care products. 7 The maximum authorized concentrations for rinse and non-rinse hair care products were 0.3% and 0.03% (w/w), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to the widespread use of 8-HQ in cosmetics and its potential toxicity to mammalian cells, European Union Council Directive 76/768/EEC stipulates that 8-HQ is not allowed to be used in cosmetics other than hair care products. 7 The maximum authorized concentrations for rinse and non-rinse hair care products were 0.3% and 0.03% (w/w), respectively. 8…”
Section: Introductionmentioning
confidence: 99%